2009
DOI: 10.1071/cp08052
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the U.S. hard red winter wheat cultivars as revealed by microsatellite markers

Abstract: Abstract. Knowledge of the genetic diversity existing in previously released hard red winter wheat (HRWW, Triticum aestivum L.) cultivars in the Great Plains region, United States, is essential for effective utilisation of these genetic resources in the various HRWW breeding programs. To ascertain a measure of the genetic diversity of the existing US HRWW, 60 cultivars were analysed with 62 microsatellite markers distributed throughout the wheat genome. Marker data were subjected to distance-based analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
7
16
0
Order By: Relevance
“…These higher allelic numbers and gene diversity information may be attributed to the use of a high number of germplasm lines, use of landraces and diverse germplasm maintained at gene bank. The PIC values revealed significant variability among different SSRs in terms of molecular polymorphism, which is in agreement to the report of Prasad et al (2009). Further computing the MI facilitated unrevealing the allelic richness of SSRs within these WSHs where chromosomes 1D, 3D and 6D possessed greater allelic richness and had slightly different (non-significant) values for MI as compared to other four D-genome chromosomes.…”
Section: Molecular Diversity Based On Ssrssupporting
confidence: 74%
See 2 more Smart Citations
“…These higher allelic numbers and gene diversity information may be attributed to the use of a high number of germplasm lines, use of landraces and diverse germplasm maintained at gene bank. The PIC values revealed significant variability among different SSRs in terms of molecular polymorphism, which is in agreement to the report of Prasad et al (2009). Further computing the MI facilitated unrevealing the allelic richness of SSRs within these WSHs where chromosomes 1D, 3D and 6D possessed greater allelic richness and had slightly different (non-significant) values for MI as compared to other four D-genome chromosomes.…”
Section: Molecular Diversity Based On Ssrssupporting
confidence: 74%
“…Genetic diversity present within winter synthetic hexaploids (WSHs) can add value by introducing new allelic variation into products where breeding and intensive selection pressure have reduced allelic diversity, causing major constraints for winter wheat improvement emerged within the modern agriculture system (Prasad et al 2009, Karsai et al 2012. The challenges faced by winter wheat breeders in the Great Plains (the largest winter wheat producing area in the USA) include moderate to high incidence of aphids, green bugs and Russian wheat aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But anyway cluster grouping gave close matches with some pedigrees and distribution of the genotypes based on the origin. Some authors such as Prasad et al (2009) had also the similar conclusions. This paper confirmed the hypothesis that the relationship of parents placed genotypes into the same groups on the basis of common alleles.…”
Section: Discussionsupporting
confidence: 63%
“…In that study, they found that genetic diversity gradually increased in cultivars released after the 1970s and cultivars released in the 1990s had the highest allelic richness. Cluster grouping gave close matches with pedigrees and with regional distribution of the cultivars (Prasad et al, 2009). Hai et al (2007) using 52 SSR markers studied genetic diversity of 69 accessions of spring bread wheat and showed that the polymorphism index content value varied from 0.24 to 0.89 with an average of 0.68.…”
Section: Introductionmentioning
confidence: 99%